Effects of the extrusion and enzymatic extrusion treatment on the apparent viscosity of degerminated maize grits - Qi, Mingming; Zhang, Dongliang; Jin, Chengqian; Chen, Shanfeng; Li, Hongjun; Ma, Chengye (International Journal of Agricultural and Biological Engineering, 2024)
Apparent viscosity is an important parameter for glucose syrup production. which is greatly affected by particle size and concentration of samples. In order to analyze the factors influencing the apparent viscosity, the particle size distribution, steady shear flow behavior, temperature, and time sweep test of native degerminated maize grits (NDMG), extruded degerminated maize grits (EDMG), and enzymatically extruded degerminated maize grits (EEDMG) with different particle sizes (passed through 20, 40, 60, 80, and 100 mesh sieves) and concentrations (water-sample ratios: 2:1, 3:1, 5:1, 10:1, and 20:1) were investigated. All samples passed through different mesh sieves showed a gradient and a relatively concentrated distribution, and slurries had typical shear-thinning properties. Apparent viscosity increased with increasing particle size and concentration. The lowest apparent viscosity was attained from the samples obtained at 100+ mesh and 20:1 water-sample ratio. Moreover, the sample with a 20:1 water-sample ratio showed the most stable apparent viscosity in the temperature sweep test. In the time sweep test, the power law equation with high determination coefficients (R2=0.9446, 0.9382) and low root mean square error (RMSE=0.0002) had the best fit to the experimental data of the EDMG and EEDMG samples passed through 100+ mesh. Overall, the lower apparent viscosities of the EDMG and EEDMG samples obtained at 100+ mesh and 20:1 water-sample ratio can improve the activity and accessibility of enzymes for glucose syrup production. This study provides critical insight into decreased apparent viscosity and expands the uses of EDMG and EEDMG in the glucose syrup sector. Keywords: degerminated maize grits, enzymatic extrusion, apparent viscosity, particle sizeDOI: 10.25165/j.ijabe.20241703.7065Citation: Qi M M, Zang D L, Jin C Q, CHen S F, Li H J, Ma C Y. Effects of the extrusion and enzymatic extrusion treatment on the apparent viscosity of degerminated maize grits. Int J Agric & Biol Eng, 2024; 17(3): 249-254.